Cognitive comorbidities in the rat pilocarpine model of epilepsy - Guarino, Annunziata; Pignata, Paola; Lovisari, Francesca; Asth, Laila; Simonato, Michele; Soukupova, Marie (Frontiers in Neurology, 2024)
Patients with epilepsy are prone to cognitive decline, depression, anxiety and other behavioral disorders. Cognitive comorbidities are particularly common and well-characterized in people with temporal lobe epilepsy, while inconsistently addressed in epileptic animals. Therefore, the aim of this study was to ascertain whether there is good evidence of cognitive comorbidities in animal models of epilepsy, in particular in the rat pilocarpine model of temporal lobe epilepsy. We searched the literature published between 1990 and 2023. The association of spontaneous recurrent seizures induced by pilocarpine with cognitive alterations has been evaluated by using various tests: contextual fear conditioning (CFC), novel object recognition (NOR), radial and T-maze, Morris water maze (MWM) and their variants. Combination of results was difficult because of differences in methodological standards, in number of animals employed, and in outcome measures. Taken together, however, the analysis confirmed that pilocarpine-induced epilepsy has an effect on cognition in rats, and supports the notion that this is a valid model for assessment of cognitive temporal lobe epilepsy comorbidities in preclinical research.